2021
DOI: 10.1111/1365-2435.13826
|View full text |Cite
|
Sign up to set email alerts
|

Consistent pattern of higher lability of leaves from high latitudes for both native Phragmites australis and exotic Spartina alterniflora

Abstract: 1. Global variation in litter decomposition rates is driven by climate, decomposer taxa and litter quality. Most large-scale studies of litter quality have made comparisons across species, rather than within a species sourced from different latitudes.Here, we aim to explore latitudinal variation in leaf litter decomposition rate and litter quality within a species.2. We investigated whether the typical interspecific pattern of increased litter lability at higher latitudes also holds within plant species, by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
(81 reference statements)
3
21
0
Order By: Relevance
“…A recent study in the Beibu Gulf region also demonstrated that the Spartina occupation reduced the diversity of macroinvertebrate assemblages on intertidal flats ( Su et al, 2020 ), and therefore may affect the availability of food sources for the juveniles ( Kwan et al, 2021 ). The presence of high tannin, phenolics and other plant defensive compounds in A. marina and S. alterniflora extracts ( Zhou et al, 2010 ; Zhang et al, 2021 ) were found to negatively affect benthic invertebrates ( Alongi, 1987 ; Lee, 1999 ), probably also reducing the rheotaxis of juvenile T. tridentatus toward these vegetations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the Beibu Gulf region also demonstrated that the Spartina occupation reduced the diversity of macroinvertebrate assemblages on intertidal flats ( Su et al, 2020 ), and therefore may affect the availability of food sources for the juveniles ( Kwan et al, 2021 ). The presence of high tannin, phenolics and other plant defensive compounds in A. marina and S. alterniflora extracts ( Zhou et al, 2010 ; Zhang et al, 2021 ) were found to negatively affect benthic invertebrates ( Alongi, 1987 ; Lee, 1999 ), probably also reducing the rheotaxis of juvenile T. tridentatus toward these vegetations.…”
Section: Discussionmentioning
confidence: 99%
“…To compare latitudinal patterns in leaf litter traits and consumption by detritivores, we focused on the invasive Spartina and the native Phragmites for the following reasons: (1) Both species are widespread (Figure S1), well studied in many ecological contexts and serve as models for the study of saltmarsh ecology and plant invasions (Ainouche et al, 2009; Cesarino et al, 2020; Eller et al, 2017; Ju et al, 2019; Li et al, 2009; Meyerson et al, 2016); (2) the distributions of both species overlap along latitudinal gradients in China (Figure S1; Zhang, Pennings, et al, 2019; Zhang et al, 2021), and the species compete when they co‐occur (Ju et al, 2017; Li et al, 2009); and (3) both species are members of the Poaceae and share several herbivores and detritivores (Chen, 2000; Qin et al, 2010; Sun et al, 2020; Xu et al, 2022), which provides a good framework for comparison of plant–animal interactions between invasive and native plants (Sun et al, 2020). We selected the isopod Porcellio laevis and the crab Chiromantes dehaani as relevant detritivores in this system.…”
Section: Methodsmentioning
confidence: 99%
“…Besides their general importance for ecosystem processes, litter traits may play a key role in the ecosystem impacts of many invasive plants. Several previous studies found higher litter decomposability for invasive than native plants (Quadros et al, 2014;Zhang et al, 2021;, but whether this is related to litter palatability to detritivores has not yet been tested. If both detritivory and decomposability are governed by litter traits, it should be possible to predict decomposition and its feedbacks to invasion by comparing the litter traits of invasive versus native plants .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations